(untitled) (Journal of the College of Basic Education, 2022)
This study is an attempt to explore the major social and moral concerns of Edward Albee (1928- ) in two of his famous plays: Who’s Afraid of Virginia Woolf ? and The Death of Bessie Smith . In these plays Albee reveals his protest against corrupt cultural values and the false concept of manhood and womanhood .He also exposes the perverted husband-wife relationships which lead to frustrations and nightmares . Themes of social inequality , racial distinction , loss and death are never absent of Albee‟s mind. In his representations of the American social life , Albee focuses on the artificial nature of many human relationships in his society .Who’s Afraid of Virginia Woolf ? is a realistic portrayal of thedominance ofthe illusive dreams of the American elite . The play is set in an American college.It presents the events of one night spent by two couples who stay up drinking after a party given by the President of the college. The four characters of the play reveal the history of their marriages.George is a middle-aged professor of History.Martha, his wife , is the daughter of the President of the college.Nick is a young professor of Biology. Honey, his wife, is a rich heiress of her father.Albee criticizes their mercenary marriages.Edward Albee believes that despite the material richness of the American society , the American civilization is essentially empty . This idea is reflected through the sterility of the characters in the play.The two families in Who’s Afraid of Virginia Woolf ? are childless.George and Martha create an illusive dream by pretending that they have a handsome child. The episode of the imaginary child is used to expose the loneliness of those people. The child does not exist at all ; it is a shared illusive dream of George and his wife to add some solace to their barren life